The Triple Frontier Again: The terrorism nexus and what has changed in the Argentinian, Brazilian, and Paraguayan borderland since 2001| A Tríplice Fronteira de novo: o nexo com o terrorismo e o que mudou na fronteira entre Argentina, Brasil e Paraguai desde 2001 - Alvino da Silva, Micael (Mural Internacional, 2019)
The Triple Frontier between Argentina, Brazil, and Paraguay has been one of the most watched areas in the Western Hemisphere since the September 11 attacks in 2001. Security experts suspect that the region's large immigrant community is linked to funding terrorist organizations, especially Hezbollah. On September 21st, 2018, the imprisonment of the Lebanese Assad Ahmad Barakat on the Brazilian side of the border, placed the Triple Frontier in the focus of analysis on the region's nexus with terrorism again. At the same time, this has been an opportunity to update some of the important changes that have taken place in this borderland since 2001. Contemporary analysis should consider demographic growth throughout the region, the end of the “sacoleiro era” and the approval of anti-terrorism laws in Argentina, Brazil and Paraguay. RESUMO A Tríplice Fronteira entre Argentina, Brasil e Paraguai é uma das áreas mais vigiadas do Hemisfério Ocidental após os ataques de 11 de setembro de 2001. Especialistas em segurança suspeitam que a numerosa comunidade de imigrantes do Oriente Médio na região tenha ligação com o financiamento de organizações terroristas, especialmente o Hezbollah. Em 21 de setembro de 2018, a prisão do libanês Assad Ahmad Barakat do lado brasileiro da fronteira colocou a Tríplice Fronteira novamente no foco de análises sobre o nexo da região com o terrorismo. Ao mesmo tempo, é uma oportunidade para atualizar algumas informações sobre mudanças importantes que ocorreram naquela borderland desde 2001. A análise contemporânea deve considerar o aumento demográfico em toda a região, o fim da “era dos sacoleiros” e a aprovação de leis antiterroristas na Argentina, no Brasil e no Paraguai. Keywords: Inter-American Relations, Terrorism, Triple Frontier. Palavras-chave: Relações Interamericanas, Terrorismo, Tríplice Fronteira. Recebido em 06 de Fevereiro de 2019 | Received on February 6, 2019 Aceito em 12 de Março de 2019 | Accepted on March 12, 2019 DOI: 10.12957/rmi.2018.39969